Glioblastoma multiforme of long survival without recurrence, case report: Glioblastoma multiforme de larga sobrevida sin recurrencia, reporte de caso - Coasaca-Torres, Juan (2018)
Introduction: Glioblastoma Multiforme (GBM) is the most common and malignant primary brain tumor. It is associated a low rate of survival and a high rate of recurrence. Despite aggressive multimodal treatment the mean overall survival is about 12 months. Nevertheless, there are reports of about 2% of cases of GBM that survive por than 36 months, they are called Long Term Survivors. Case report: On 2014 a 25-year-old male was treated by complete resection of a right parieto-occipital brain tumor. The results from patology was Glioblastoma Multiforme. The patient underwent through chemotherapy and radiotherapy after surgery. After more than 3 years the patient has a Karnofsky scale score (KPS) of 100 and without recurrence of the disease. Discussion: There is a low percentage of cases of GBM that survive more than 36 months. This survival has been related with some prognostic factors such as age, preoperative status (KPS) and complete resection of the lesion. However, there are still other genetic and molecular factors that have to be elucidated. Conclusion: There is a chance of long term survival of patients with the diagnosis of Glioblastoma Multiforme it is so that, taking into account the prognostic factors, neurosurgeons should treat this disease aggressively understanding that the only known modifiable factor is the complete surgical resection. Key words: Glioblastoma multiforme; Prognostic factors; Long survival; Recurrence case report. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1290